Leaf flavonoid content in Quercus ilex L. resprouts and its seasonal variation - Brossa, R.; Casals, I.; Pintó-Marijuan, M.; Fleck, I. (Trees, 2008)
Here, we provide the ﬁrst report on ﬂavonoid content in holm oak (Quercus ilex L.) leaves, analyzed by HPLC–MS/MS. Flavanols and ﬂavonols were the predominant groups, although proanthocyanidins and many soluble tannins had a relevant presence in all leaf samples. Seasonal variation of ﬂavonoids was determined in extracts from Q. ilex leaves during resprouting after a forest ﬁre in two Mediterranean forests. Similar seasonal trends were observed over 2 years during the two main stress seasons (winter and summer). The most abundant ﬂavonoid was the ﬂavanol epicatechin, which showed similar values during the two seasons. Hexosides of the ﬂavonols, quercetin, kaempferol and rhamnetin showed considerably higher content in winter, especially at the lowest temperatures. These variations in both forests are discussed on the basis of the chlorophyll ﬂuorescence results obtained. Anthocyanins were found practically absent in mature leaves. Nutrient or water availability differences between sites or seasons were not related to changes in leaf ﬂavonolhexoside content.
Keywords: á; á hplc; chlorophyll fluorescence; chlorophyll fluorescence á flavanols; esi; flavanols; flavonol-hexosides; flavonol-hexosides á holm oak; Holm oak; HPLC–ESI–MS/MS; ms

Leaf flavonoid content in Quercus ilex L. resprouts and its seasonal variation - Brossa, R.; Casals, I.; Pintó-Marijuan, M.; Fleck, I. (Trees, 2008)
Here, we provide the ﬁrst report on ﬂavonoid content in holm oak (Quercus ilex L.) leaves, analyzed by HPLC–MS/MS. Flavanols and ﬂavonols were the predominant groups, although proanthocyanidins and many soluble tannins had a relevant presence in all leaf samples. Seasonal variation of ﬂavonoids was determined in extracts from Q. ilex leaves during resprouting after a forest ﬁre in two Mediterranean forests. Similar seasonal trends were observed over 2 years during the two main stress seasons (winter and summer). The most abundant ﬂavonoid was the ﬂavanol epicatechin, which showed similar values during the two seasons. Hexosides of the ﬂavonols, quercetin, kaempferol and rhamnetin showed considerably higher content in winter, especially at the lowest temperatures. These variations in both forests are discussed on the basis of the chlorophyll ﬂuorescence results obtained. Anthocyanins were found practically absent in mature leaves. Nutrient or water availability differences between sites or seasons were not related to changes in leaf ﬂavonolhexoside content.
Keywords: á; á hplc; chlorophyll fluorescence; chlorophyll fluorescence á flavanols; esi; flavanols; flavonol-hexosides; flavonol-hexosides á holm oak; Holm oak; HPLC–ESI–MS/MS; ms